Question

Use Laplace Transforms to solve the given initial value problem y''-4y'+4y=t^3e6(2t) y(0)=1 and y'(0)=-2

Answer #1

Solve the initial value problem using Laplace transforms y "+
2ty'-4y = 1; y (0) = y '(0) = 0.

Use Laplace transforms to solve the given initial value
problem.
y"-2y'+5y=1+t y(0)=0 y’(0)=4

y'' - 4y' + 4y = (6)(e^(2t)) y(0)=y'(0)=0
Use Laplace Transforms to solve. Sketch the solution or use
matlab to show the graph.

y'' + 4y' +4y = e^(-2t) y(0)=0 y'(0)=4
Use Laplace Transforms to solve. Sketch the solution or use
matlab to show the graph.

Solve the initial value problem below using the method of
Laplace transforms. y"+11y'+30y=280e^2t, y(0)=1, y'(0)=32

Use the method of laplace transforms to solve the following
Initial Value Problem:
y"+2y'+y=g(t), y'(0)=0

Use Laplace Transforms to solve the following IVPs .
4y′′+4y′+5y=−t ; y(0)=0 , y′(0)=0

use the laplace transform to solve initial value
problem
y"+4y'+20y=delta(t-2)
y(0)=0, y'(0)=0
use step t-c for uc(t)

Use the Laplace transform to solve the given initial-value
problem. Use the table of Laplace transforms in Appendix III as
needed.
y'' + 25y = cos 5t, y(0) =
3, y'(0) = 4

Use the method of Laplace transforms to solve the following
initial value problem. y'' + 6y' + 5y = 12e^t ; y(0) = −1, y'(0) =
7

ADVERTISEMENT

Get Answers For Free

Most questions answered within 1 hours.

ADVERTISEMENT

asked 11 minutes ago

asked 15 minutes ago

asked 19 minutes ago

asked 36 minutes ago

asked 50 minutes ago

asked 56 minutes ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 1 hour ago

asked 2 hours ago